Analysis of pulmonary embolus size at the time of recurrence compared with presentation: a single‐centre retrospective study. (24th May 2017) - Thomas, W.; Firth, O.; Besser, M.; Beveridge, M.; Baglin, T.
Abstract : Essentials Size of pulmonary embolus (PE) at the time of recurrence compared with first event is unstudied. In a retrospective cohort of patients we compared PE size at recurrence versus the initial PE. Rates of massive PE at recurrence were low whether the first PE was massive or unmassive. Studies to determine PE size and severity at recurrence when anticoagulation is stopped are needed. Summary: Background: The size of recurrent pulmonary embolus (PE) in relation to a prior event could be a factor in deciding whether to continue anticoagulation. There are no published data on this subject to help with counselling patients. Objectives: To determine whether size of a first PE predicts the size at recurrence. Patients and methods: This was a retrospective cohort study of consecutive patients with recurrent PE over 25 months at a single tertiary center. In confirmed cases the sizes of first and recurrent PEs were grouped into radiologically non‐massive PE (RNMPE) or radiologically massive PE (RMPE) if there was bilateral main pulmonary artery thrombus, saddle PE or right ventricular strain on the computerized tomography pulmonary angiogram. Results: Sixty‐three patients were included in the study (37 exclusions). Thirty‐seven patients were men and 26 women, with a median age of 72 years; 33.3% of PEs were unprovoked. Patients whose first PE was an RNMPE (46/63 or 73% of patients) had a 15.2% (95% confidence interval [CI], 7.6–28.2%) chance of RMPE at recurrence and a 32.6% (95% CI 20.9–47.0%) chance of having a larger PE at recurrence, whereas those who presented first with an RMPE (17/63 or 27% or patients) had a 17.6% (95% CI, 6.2–41.0%) chance of RMPE at recurrence (odds ratio, 1.19; CI, 0.27–5.27). Conclusions: Risk of a massive PE at recurrence is low (and similar) irrespective of the size of the first PE in this single study. Further studies are warranted as this could help in decisions on long‐term anticoagulation.